2005
DOI: 10.1128/jvi.79.15.9685-9693.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Polerovirus Minor Capsid Protein Determines Vector Specificity and Intestinal Tropism in the Aphid

Abstract: Aphid transmission of poleroviruses is highly specific, but the viral determinants governing this specificity are unknown. We used a gene exchange strategy between two poleroviruses with different vectors, Beet western yellows virus (BWYV) and Cucurbit aphid-borne yellows virus (CABYV), to analyze the role of the major and minor capsid proteins in vector specificity. Virus recombinants obtained by exchanging the sequence of the readthrough domain (RTD) between the two viruses replicated in plant protoplasts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
51
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 43 publications
0
51
0
Order By: Relevance
“…This was not surprising considering that previous work had shown that virions of BYDV devoid of the RTP were able to cross the gut barrier, indicating that the CP possessed the determinants for mediating gut uptake (Chay et al, 1996). However, RTP can affect the efficiency of virus transport across the gut (Brault et al, 2000(Brault et al, , 2007Reinbold et al, 2001) and RTP can determine intestinal tropism when mediating acquisition (Brault et al, 2005).…”
Section: Aphid Transmission Of the Rtd Mutants Via Tissue Feeding Andmentioning
confidence: 99%
“…This was not surprising considering that previous work had shown that virions of BYDV devoid of the RTP were able to cross the gut barrier, indicating that the CP possessed the determinants for mediating gut uptake (Chay et al, 1996). However, RTP can affect the efficiency of virus transport across the gut (Brault et al, 2000(Brault et al, , 2007Reinbold et al, 2001) and RTP can determine intestinal tropism when mediating acquisition (Brault et al, 2005).…”
Section: Aphid Transmission Of the Rtd Mutants Via Tissue Feeding Andmentioning
confidence: 99%
“…The icosahedral virions contain a positive sense, singlestranded RNA encapsidated by two proteins: a major 22 kDa coat protein and a minor 72 kDa read-through protein. Both proteins are involved in regulating virus transmission efficiency (Van den heuvel et al, 1993;Chay et al, 1996;Gildow, 1999;Brault et al, 2005). Luteoviruses are phloem limited and transmitted from plant to plant solely by aphids in a circulative, non-propagative manner (Gray and Gildow, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…ORF3 encodes the coat protein (CP) and completely contains ORF4, which is not found in Enamovirus and is needed for virus movement in the plant (the movement protein, MP). ORF5, which is necessary for aphid transmission (6,27,49) and is also involved in virus movement (57) and Luteoviridae phloem limitation (58), is translated through in-frame read-through of the ORF3 stop codon, existing as a read-through domain (RTD) fused to the CP. Members of the genus Polerovirus have an extra ORF0 in the 5Ј end of the genome partially overlapping ORF1.…”
mentioning
confidence: 99%